A Schrödinger cat-like state laser with zero diffusion - de Oliveira Neto, F.; de Ponte, M. A. [UNESP]; Moussa, M. H.Y. (Springer Nature, 2023)
A method for building a Schrödinger cat-like state laser is here proposed which follows from the introduction of a particular reservoir engineering technique into the laser theory. Our method demands the building of an effective atom-field interaction in addition to the construction of an isomorphism between the cavity field operators in both the effective and the Jaynes-Cummings Hamiltonians. In other words, we build an isomorphism between the field operators of the conventional laser theory and those of our effective laser, in such a way that the stationary solution of the latter laser follows immediately from that of the former. Our Schrödinger Cat-like state laser presents zero diffusion from cavity losses.